Selected physiological and perceptual responses of batsmen during a simulated one day international century : impact on performance,Selected physiological and perceptual responses of batsmen during a simulated oen day international match - Pote, Lee (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Background: Very few studies have examined the demands of prolonged batting on physical, psychophysical and performance responses. Objective: The purpose of this study was therefore to determine the physiological and perceptual responses of batsmen scoring a simulated One Day International century. Furthermore, the impact that these responses had on batting performance were also measured. Methods: Seventeen male cricketers currently playing for Rhodes University or the country districts side, performed a simulated bating innings (BATEXÂ©), typical of scoring a One Day international century. The BATEXÂ© protocol consisted of six, five over stages (21 minutes each), with each stage matched to a specific phase of play where batsmen were encouraged to bat with the mindset of that phase. During stages one, three and five players ran at a "self-selected cruise pace" whereas during stages two, four and six players were required to run at maximum speed. At set intervals, selected physiological, perceptual and performance measures were recorded. Results: Most physiological responses increased and decreased accordingly with the low and high intensity stages with the exception of respiratory exchange ratio and core temperature responses. Mean physiological responses however, showed a progressive rise over time. Central ratings of perceived exertion increased as a function of intensity and duration. Sprint times got slower as the protocol progressed, while accuracy (impact accuracy) improved significantly (p<0.05) after stage one and then stabilised for the remainder of the protocol. Conclusion: The simulated batting protocol significantly impacted the physiological and perceptual responses over time. This was due to both the intensity and the duration of the work-bout. Furthermore, the increased physiological load placed on the batsmen significantly impacted the physical performance of the batsmen. An increase in sprint times (players getting slower) towards the end of the protocol may indicate the presence of physical fatigue. This physical fatigue did not however seem to impact the batsmen cognitively as accuracy improved after the first stage and then remained constant over time.
Keywords: Cricket -- Batting; Sports -- Physiological aspects; Sports -- Psychological aspects